(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This review paper is devoted to the nuclear arms race between Pakistan and India, focusing on the areas in which it is taking place and the consequences arising from it. The purpose of this study is to reveal the dynamics of nuclear armament and its impact on related areas and threats to regional security. Also, an attempt was made to cover the consequences arising from the recent crisis within the framework of the study. The issue of the nuclear arms race is approached from the perspective of the security dilemma and the action-reaction model theory, and it is emphasized that this process is a negative phenomenon both regionally and globally. At the same time, we consider this topic to be extremely relevant, and we consider it appropriate to refer to it again and again over time, to study the transformation of this process.